2021
DOI: 10.1002/rcr2.760
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural fibrinolysis in acute non‐traumatic retained haemothorax

Abstract: Haemothorax is an accumulation of blood in the pleural space. Retained haemothorax refers to blood that cannot be drained from the pleural cavity and is associated with an increased risk of empyema and fibrothorax often necessitating surgical evacuation. We describe our experience of using intrapleural fibrinolytic therapy in three patients with different bleeding risk and acute non‐traumatic retained haemothorax. The first was a 41‐year‐old female with disseminated Candida guilliermondii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…One patient with infected residual traumatic haemothorax was successfully drained with 20 mg of alteplase without significant bleeding, as reported by Fernandes et al 11. Foo and Herre et al reported successful response to intrapleural tPA (10 mg) administered 12 hours apart in one patient with persistent iatrogenic haemothorax and another patient with spontaneous haemothorax, without any reported complications 12. A randomised control trial is needed to evaluate the efficacy of intrapleural tPA/DNase in postsurgery-related complex effusion as an alternative therapy to VATS decortication.…”
Section: Discussionsupporting
confidence: 55%
“…One patient with infected residual traumatic haemothorax was successfully drained with 20 mg of alteplase without significant bleeding, as reported by Fernandes et al 11. Foo and Herre et al reported successful response to intrapleural tPA (10 mg) administered 12 hours apart in one patient with persistent iatrogenic haemothorax and another patient with spontaneous haemothorax, without any reported complications 12. A randomised control trial is needed to evaluate the efficacy of intrapleural tPA/DNase in postsurgery-related complex effusion as an alternative therapy to VATS decortication.…”
Section: Discussionsupporting
confidence: 55%
“…Almost all prior data on the use of IPFT has been extracted from traumatic hemothorax use [ 14 , 15 ], and the role of IPFT in management of non-traumatic hemothorax remains unknown. This report along with one prior case series describing the successful use of IPFT in three patients who developed non-traumatic retained hemothorax [ 16 ] demonstrates the potential safety and efficacy of IPFT in the management of retained hemothorax when used in the right environment and appropriate patient population.…”
Section: Discussionmentioning
confidence: 72%